Survei Minat Olahraga Bola Voli Remaja di Kecamatan Ambal Tahun 2025: Penelitian - Irfan Maulana; Rahmawan Santoso (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sports especially volleyball is the 2nd most popular sport after football, this volleyball game is also very popular among young men and women. According to them this game is very interesting and becomes its own entertainment, with the existence of volleyball sports activities has an impact on the decline in negative activities carried out by teenagers in the Ambal sub-district. The interest of teenagers in participating in volleyball sports activities is very high as evidenced by the average answer to the questionnaire at 91% this is also a reference so that teenagers live healthier and reduce negative activities. Teenagers also need encouragement from outside such as from friends, teachers, family, the environment and also adequate infrastructure.